Greenlash in the media - Yingnian Tao; Mark Ryan (Humanities & Social Sciences Communications)
Abstract This study uses metadata visualisation and corpus linguistics to examine patterns of representation of the emerging term greenlash in media reports, as retrieved from the Nexis news database. The metadata analysis reveals that media coverage of greenlash has surged since 2021, predominantly in left leaning European and North American media sources. Through Sketch Engine, collocation analysis identified core thematic areas surrounding greenlash: definition and resistance, status, actor, cause and impact, and location. Our findings indicate that greenlash is primarily a European phenomenon, which may be attributed to a lack of mainstream outlets through which actors can voice opposition to climate policies. The phenomenon is largely driven by economic concerns, in response to specific policies perceived to impose financial burdens on protesting groups. Moreover, our analysis reveals that media organisations often introduce the term greenlash as broad, generalised public opposition to environmental policies rather than a complex, economically driven opposition to specific policies, and portray this opposition in a negative light. We suggest that media organisations may downplay these elements in opposition to neoliberal or populist ideologies or to retain readership. This phenomenon thus highlights the complex intersection between environmental policies, economic burdens, and political divisions underscoring the broader tensions and paradoxes surrounding climate action and socio-economic disparities.